A Crystalline Supramolecular Rotor Functioned by Dual Ultrasmall Polar Rotators†. Issue 16 (8th June 2022) - Li, Wang; Liu, De‐Xuan; Hu, Wei‐Yu; Liu, Qing‐Yan; Du, Zi‐Yi; He, Chun‐Ting; Zhang, Wei‐Xiong; Chen, Xiao‐Ming
Comprehensive Summary: As an extended model of conventional molecular rotors, a conceived construction of novel crystalline molecular rotor that simultaneously contains two discrete polar rotators is presented here. The supramolecular self‐assembly of 18‐crown‐6 host and two rotator‐containing ion‐pair guests affords a three‐in‐one cocrystal, (2‐NH3 ‐ i BuOH)(18‐crown‐6)[ZnBr3 (H2 O)], in which the hydroxyl group and aqua ligand both function as ultrasmall polar rotators. On the basis of the variable‐temperature single‐crystal X‐ray diffraction, variable‐temperature/frequency dielectric response, density functional theory calculations, and molecular dynamics simulations, it is found that such dual polar rotators experience a gradually enhanced rotation with increasing temperature, and more importantly, could be controlled by a reversible polar‐to‐polar structural phase transition, i.e., from a "single‐(polar rotator)" state at low‐temperature phase to a "mixed‐dual‐(polar rotator)" state in the vicinity of transition, and to an unusual "synchronized‐dual‐(polar rotator)" state at high‐temperature phase. Abstract : As an extended model of conventional molecular rotors, a novel crystalline supramolecular gyroscope (2‐NH3 ‐ i BuOH)(18‐crown‐6)[ZnBr3 (H2 O)] functioned by dual polar rotators is reported here, in which both the hydroxyl group and aqua ligand can experience gradually enhanced rotations upon heating.